KEPUTUSAN LAJNAH TARJIH MUHAMMADIYAH DAN LAJNAH BAHSUL MASAâIL NAHDLATUL ULAMA SEBAGAI KEPUTUSAN IJTIHAD JAMAâI INDONESIA - Sirajuddin, Azmi (STAIN Jurai Siwo Metro, 2004)
Ijtihad (Independent Judgment in Legal Questions) is a source of the Islamic law. In the past, the ijtihad was made individually, but in modern time it is probably conducted collectively (Jamaâi). The Muhammadiyahâs Committee of the Tarjih (taking a preponderant legal opinion) and the NUâs Committee of the Bahth al-Masaâil (Research on the Relegious Questions) are actually two institutions of the Ijtihad jamaâi (Collective independent Judgment in Legal Questions) in Indonesia. Each instution repesenting opinion of Muhammadiyah and NU organizations has in principle the same concept of Islamic law, but they have differences in the methodology of formulating the law.Â Keyword : Decisions, Ijtihad JamaâiÂ